3D-printed devices for continuous-flow organic chemistry - Dragone, Vincenza; Sans, Victor; Rosnes, Mali H.; Kitson, Philip J.; Cronin, Leroy (Beilstein Journal of Organic Chemistry, 2013)
We present a study in which the versatility of 3D-printing is combined with the processing advantages of flow chemistry for the synthesis of organic compounds. Robust and inexpensive 3D-printed reactionware devices are easily connected using standard fittings resulting in complex, custom-made flow systems, including multiple reactors in a series with in-line, real-time analysis using an ATR-IR flow cell. As a proof of concept, we utilized two types of organic reactions, imine syntheses and imine reductions, to show how different reactor configurations and substrates give different products.
Keywords: 3D printing; flow chemistry; flow IR; in-line analysis; imine reduction; imine synthesis; millifluidics; reactionware